How Psychological Comfort and Aesthetic Value Influence Purchase Decision in Dental Clinic Services: The Mediating Role of Price Perception - Tri Adi Santosa; Osly Usman (Journal of Digital Business and Global Economy, 2026)
This study aims to examine the influence of psychological comfort and aesthetic value on purchase decision in dental clinic services, with price perception serving as a mediating variable. We used quantitative explanatory research design and data analysis with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that psychological comfort and aesthetic value have positive and significant effects on both price perception and purchase decision. Furthermore, price perception positively influences purchase decision and partially mediates the relationships between psychological comfort, aesthetic value, and purchase decision. The structural model demonstrates substantial explanatory power in predicting patients’ decisions to utilize dental clinic services. The findings reveal that psychological comfort is the most influential factor affecting purchase decision, exceeding the influence of aesthetic value. These results highlight the importance of creating a comfortable emotional environment, reducing patient anxiety, and enhancing the perceived aesthetic benefits of dental services. The study provides practical implications for dental clinic managers in developing patient-centered service strategies that strengthen perceived value and encourage service utilization.